Governing through consensus? The European semester, soft power and education governance in the EU - Eeva, K (SAGE Publications, 2021)
This paper discusses the workings of the European Semester (ES) in relation to the policy field of education. My study shows how the ES enables the steering of education policy through encouraging specific economic and employment-related actions by European Union (EU) member states. With a focus on the relationship between the EU institutions and member states, this paper examines how the ES discursively promotes certain approaches to education through country-specific recommendations (CSRs). In this study, CSRs are revealed as policy spaces where European and national interests are brought together, enabling shared problem definition and collective learning. The paper illustrates how policy moves through translation and negotiation in the construction of CSR. The evidence drawn on here comes from analysis of CSRs in 2011–2016 and 15 semi-structured interviews with key policy actors, mainly from the European Commission, Council and Parliament. This paper concludes that CSRs work through soft power to manage governing tensions through translation and by building convergence and consensus. The analysis is framed theoretically by research on governing and knowledge and draws on a social constructivist perspective on policy work.